PERFORMANCE ANALYSIS OF THE IMPLEMENTATION OF TECHNOLOGY SERVICES ON INTERACTIVE VOICE RESPONSE PHONE BANKING IN THE BANK X - Fivtatianti Fivtatianti Hendajani (STMIK Jakarta, 2004)
Current technological developments are very advanced and widely adopted in variousfields. An example is the banking sectorPhone banking services of Bank X uses technology Interactive Voice Response (IVR)which provides convenience for customers to conduct banking transactions via the telephoneassistance without any time limit. Since its application requires a lot of cost performanceanalysis, we need to hold these services in order to be more about the target market segmentin question.The analysis was made with the help of data in the form of transaction data, phone bankingservices of Bank X in order to reach conclusions that lead to improvements in customerservice.